Photoperiod affects gamete production, and protein and lipid metabolism in male narrow-clawed Crayfish Pontastacus leptodactylus (Eschscholtz, 1823) - Farhadi, Ardavan; Harlioglu, Muzaffer Mustafa (Elsevier, 2019)
Understanding effects of photoperiod on the reproductive efficiency and physiological responses of Pontastacus leptodactylus is important for successful management of the crayfish hatcheries. Spermatozoal number, gonado-somatic index (GSI), hepatosomatic index (HSI), testicular index (TI), vas deferens index (VDI), and total protein, amino and fatty acid profiles of the hepatopancreas were evaluated in male narrow-clawed crayfish P. leptodactylus. Animals (30-70 g) were maintained utilizing five different photoperiodic regimens (3 L:21D, 6L:18D, 24 L:OD, 0L:24D, and natural photoperiod (9 L:15D)) for 5 weeks. Different photoperiods affected spermatozoal number, GSI, and total protein, amino acid and fatty acid profiles of the hepatopancreas (P < 0.05). The greatest spermatozoal number and GSI were recorded in darkness (P < 0.05). There was the least spermatozoal number (3.5 x 10(6) +/- 0.5) and GSI (2 +/- 0.1%) when imposing the 9 L and 24 L photoperiodic regimens, respectively. In addition, maintenance in constant light as compared with other lighting regimens resulted in a greater total protein (43.68 +/- 4.83 mg/g), phenylalanine (7.23 +/- 0.35%), and total single unsaturated fatty acids (Sigma MUFA) (48.07 +/- 2.30%), but lesser total polyunsaturated fatty acids (Sigma PUFA) (23.36 +/- 1.07%), serine (1.53 +/- 0.02%), Sigma n-6 (11.24 +/- 1.18%), 20:4 (n-6) (2.7 +/- 0.14%), and 20:2 (0.67 +/- 0.17%) contents in the hepatopancreas (P < 0.05). The results of the present study indicate total darkness increases the spermatozoal production and imposing longer dark periods improved the reproductive efficiency and physical conditions in male P. leptodactylus.
Keywords: Amino acid; Decapoda; Fatty acid; Hepatopancreas; Reproductive efficiency